Identity Politics Practice Through Dominant Discourse "Sitiarjo Village As A Christian Village" in Local Politics Dynamics - Anisa Dwi Istiningrum (Jurnal Partisipatoris, 2021)
GKJW Christian figures are groundbreakers or founders of Sitiarjo Village, so that the GKJW Christians have a higher position compared to other religions followers. On this basis, many policies are considered religious bias. The purpose of this research is to explain the practice of identity politics in local politics in Sitiarjo Village. This study uses the identity politics concept. This research method is a qualitative with case study approach. Data analysis techniques used is pattern matching. The results of this study state that identity politics in the local politics dynamics in Sitiarjo Village seems to be getting stronger because anyone who wants to get involved in politics must consider this religious issue. Because in the view of the society, GKJW Christians must receive top priority to enter into structural positions in the village government, including becoming village head. This made the communalism issue, such as religious sentiment, even stronger in Sitiarjo Village.